Chronic Kidney Disease Detection Using Micro-service Architecture (International Journal of Innovative Research in Computer Science & Technology, 2019)
In this proposed project, the patients will  perform the registration, once the patient is registered  into the application then the patients are allowed to  enter there scanning attributes of kidney diseases and  then the user kidney disease stage level is determined by  making use of C5.0 and Naïve Bayes supervised  machine learning algorithm, the system provides, the  user will get suggestions from the doctor at various level  of kidney stage and if the user belongs to kidney stage 5  then patient will get suggestions patient will get  suggestions as well as appointment request.
Keywords: chronic kidney disease; C5.0; Naïve Bayes; scanning attributes